Antimicrobial susceptibility patterns and plasmid profile of vibrio species from processed and unprocesssed food grade crab - Aigbodion, Omogbai Barry; Nnenji, Obichi Cynthia (Food and Applied Bioscience Journal, 2017)
Antimicrobial susceptibility patterns and plasmid profiles of Vibrio species isolated from edible crabs (Callinectes sapidus) were evaluated. A total of 40 crabs and the obtained water samples collected from four different markets in Lagos State were examined. Morphological and biochemical techniques were used to identify the Vibrio spp present in the samples. Susceptibility of bacteria isolates to 8 antibiotics was studied using a disc diffusion method and plasmid profile was determined by agarose gel electrophoresis. The total viable Vibrio count in unprocessed samples ranged from 3.30 to 5.80 Log10cfu/g while the processed ones was 1.80 to 2.5 Log10cfu/g. The identified Vibrio spp included, V. cholerae, V. harveyi. V. mimicus, V. parahaemolyticus, V. furnissii and V. fluvalis. Results revealed that Vibrio isolates from the samples expressed total (100%) antibiotic resistance to amoxcycilin and augumentin, 83.3% to cotrimoxazole, 72.2% to tetracycline, 66.6% to nitrofurantoin, 61.6% to gentamicin, 33.3% to nalidilixic acid and no resistance to ofloxacin. The isolates had a multiple antibiotic resistance (MAR) index ranging from 0.25–0.88. Plasmid profile of 10 isolates which showed multiple resistance to antibiotics revealed that 7 harboured plasmid with bands ranging from 23130 bp – 20240 bp as molecular weight. Isolation of Vibrio spp from seafood of this nature is considered as a potential danger for consumers.